Modeling the vertical distribution of soil organic carbon in temperate forest soils on the basis of solute transport - Yu, Fang; Liu, Qiang; Fan, Chunnan; Li, Shuang (Frontiers in Forests and Global Change, 2023)
Temperate forests are of pivotal importance in global carbon cycle, as they currently act as a carbon sink. Moreover, the continued expansion of the forest provides significant benefits in terms of mitigating climate change. Soil organic carbon (SOC) constitutes a vital component of the carbon inventory harbored within forest soils. Thus, understanding the dynamics and distribution of SOC in temperate forest soils can be essential to better predict the forest SOC inventories, and can help to provide theoretical basis for further studies in soil carbon management technologies. Spatial variability of SOC has been studied extensively, but the mechanism that regulates the vertical pattern of SOC is still not clear. In the present study, we hypothesized that the vertical pattern of SOC in temperate forest soils is dominated by the vertical transport of solute in soil, and a theoretical vertical scaling of SOC was proposed based on percolation theory. Theoretical range of SOC in the national forests in northeastern China and the United States were also predicted. The agreement between the observed SOC profiles and the theoretical scaling supported the hypothesis and suggested that percolation theory can be applied to depict the vertical distribution of SOC, while the application could be limited if vegetation cover and soil texture alter the dominant controlling factor of SOC distribution. The concordance between empirical data and the predicted range also showed significant potential of integrating percolation theory into comprehensive models for carbon stock estimation.